FEATURES OF THE COURSE OF TONSILLITIS IN CHILDREN INFECTED WITH THE HERPES VIRUS (World Science, 2020)
The article presents the features of the clinical course of tonsillitis caused by hemolytic streptococcus in children infected with human herpes simplex virus type 6 (HHV 6). It was revealed that tonsillitis in children with background infection with HHV 6 is characterized by a prolonged course, prolonged maintenance of fever, impaired general condition, the presence of signs of hepatomegaly and regional lymphadenitis, and as a result, a longer stay of such patients in the hospital. The characteristic clinical and laboratory features of tonsillitis in children infected with HHV 6 include the presence in the debut of the disease subfebrile body temperature, regional lymphadenopathy, hepatomegaly, thrombocytopenia, signs of a parenchymal reaction of the liver and mesadenitis. Latent HHV 6 infection in children affects the frequency of registration and the duration of certain symptoms of tonsillitis.